Randomized controlled trial of topical corticosteroid and home‐based narrowband ultraviolet B for active and limited vitiligo: results of the HI‐Light Vitiligo Trial. (1st May 2021) - Thomas, K.S.; Batchelor, J.M.; Akram, P.; Chalmers, J.R.; Haines, R.H.; Meakin, G.D.; Duley, L.; Ravenscroft, J.C.; Rogers, A.; Sach, T.H.; Santer, M.; Tan, W.; et al.
Summary: Background: Evidence for the effectiveness of vitiligo treatments is limited. Objectives: To determine the effectiveness of (i) handheld narrowband UVB (NB‐UVB) and (ii) a combination of potent topical corticosteroid (TCS) and NB‐UVB, compared with TCS alone, for localized vitiligo. Methods: A pragmatic, three‐arm, placebo‐controlled randomized controlled trial (9‐month treatment, 12‐month follow‐up). Adults and children, recruited from secondary care and the community, aged ≥ 5 years and with active vitiligo affecting < 10% of skin, were randomized 1 : 1 : 1 to receive TCS (mometasone furoate 0·1% ointment + dummy NB‐UVB), NB‐UVB (NB‐UVB + placebo TCS) or a combination (TCS + NB‐UVB). TCS was applied once daily on alternating weeks; NB‐UVB was administered on alternate days in escalating doses, adjusted for erythema. The primary outcome was treatment success at 9 months at a target patch assessed using the participant‐reported Vitiligo Noticeability Scale, with multiple imputation for missing data. The trial was registered with number ISRCTN17160087 on 8 January 2015. Results: In total 517 participants were randomized to TCS ( n = 173), NB‐UVB ( n = 169) and combination ( n = 175). Primary outcome data were available for 370 (72%) participants. The proportions with target patch treatment success were 17% (TCS), 22% (NB‐UVB) and 27% (combination). Combination treatment was superior to TCS: adjusted between‐group difference 10·9% (95% confidence interval 1·0%–20·9%; P = 0·032; number needed to treat = 10). NB‐UVB alone was not superior to TCS: adjusted between‐group difference 5·2% (95% CI − 4·4% to 14·9%; P = 0·29; number needed to treat = 19). Participants using interventions with ≥ 75% expected adherence were more likely to achieve treatment success, but the effects were lost once treatment stopped. Localized grade 3 or 4 erythema was reported in 62 (12%) participants (including three with dummy light). Skin thinning was reported in 13 (2·5%) participants (including one with placebo ointment). Conclusions: Combination treatment with home‐based handheld NB‐UVB plus TCS is likely to be superior to TCS alone for treatment of localized vitiligo. Combination treatment was relatively safe and well tolerated but was successful in only around one‐quarter of participants.